Integrating Islamic Educational Values and Teacher Professional Formation: A CIPP-Based Evaluation in Contemporary Contexts - Yuyun Zunairoh; Fartika Ifriqia; Ahmad Badrus (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study critically evaluates the implementation of the Professional Teacher Education Program (PPG) within an Islamic higher education context using the Context, Input, Process, and Product (CIPP) model, with a particular focus on how Islamic educational values shape teacher professional formation. This research employs a qualitative case study design involving program administrators, lecturers, mentor teachers, and participants. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using thematic analysis aligned with the CIPP framework. The findings suggest that the PPG program is institutionally robust and contextually relevant in addressing the demand for certified teachers. However, recent efficiency-oriented transformations have reduced opportunities for reflective learning, intensive mentoring, and value internalization. Islamic educational values are systematically embedded in curriculum design, pedagogical interaction, and the formation of professional teacher identity. This study reconceptualizes Islamic educational values not as supplementary elements but as structuring principles that shape all dimensions of program evaluation within the CIPP framework. The study advances an integrative evaluation framework linking professional competence, ethical orientation, and institutional identity, while contributing to global discussions on culturally responsive teacher education.